Data analytics and management in data intensive domains : 20th international conference, DAMDID/RCDL 2018, Moscow, Russia, October 9-12, 2018, revised selected papers /: 20th international conference, DAMDID/RCDL 2018, Moscow, Russia, October 9-12, 2018, revised selected papers. (2019) - Unknown
No abstract available